2016
DOI: 10.17512/jamcm.2016.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Drag on a permeable sphere placed in a micropolar fluid with non-zero boundary condition for microrotations

Abstract: Abstract. This paper concerns an analytical study of an infinite expanse of uniform flow of steady axisymmetric creeping flow of an incompressible micropolar fluid around the permeable sphere assuming a nonhomogeneous boundary condition for microrotation vector. It is assumed that microrotation vector is proportional to the rotation rate of velocity vector. The stream function solutions for the flow fields are obtained in the terms of modified Bessel's functions and Gegenbauer functions. Continuity of normal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Satya Deo and Pankaj Shukla [5] calculated the drag generated by a liquid sphere with non-newtonian liquid moving over it with a non-homogeneous micro rotation vector on the boundary by using an analytic method. Jaiswal and Gupta [6] conducted a sustainable analysis of the steady axisymmetric creeping flow of an incompressible non-Newtonian liquid beyond an immersible Reiner-Rivlin liquid sphere and noticed that the cross-viscosity raises the drag on the Reiner-Rivlin sphere in the non-Newtonian liquid. Pankaj Shukla [7] discussed how the laminar flow of a non-Newtonian liquid beyond a sphere enclosed with a slim liquid sheet and obtained the drag force using a non-zero spin boundary condition for the micros-rotation vector.…”
Section: Introductionmentioning
confidence: 99%
“…Satya Deo and Pankaj Shukla [5] calculated the drag generated by a liquid sphere with non-newtonian liquid moving over it with a non-homogeneous micro rotation vector on the boundary by using an analytic method. Jaiswal and Gupta [6] conducted a sustainable analysis of the steady axisymmetric creeping flow of an incompressible non-Newtonian liquid beyond an immersible Reiner-Rivlin liquid sphere and noticed that the cross-viscosity raises the drag on the Reiner-Rivlin sphere in the non-Newtonian liquid. Pankaj Shukla [7] discussed how the laminar flow of a non-Newtonian liquid beyond a sphere enclosed with a slim liquid sheet and obtained the drag force using a non-zero spin boundary condition for the micros-rotation vector.…”
Section: Introductionmentioning
confidence: 99%
“…A study of a Couple acting on a couple-stress uid for rotary ows across a permeable sphere was carried out [8]. Vandana Mishra and Ram Gupta [9] studied the concept of analytically uniform ow of steady axi-symmetric creeping ow of an incompressible micro-polar uid around the permeable sphere. They considered non homogeneous boundary conditions for micro-rotation vector.…”
Section: Introductionmentioning
confidence: 99%
“…The slow steady rotation of micropolar fluid sphere in concentric spherical container using non-zero boundary condition for microrotation vector was solved by Madasu and Gurdatta (2015) and they obtained the hydrodynamic couple and wall correction factor exerted on the micropolar fluid. Mishra and Gupta (2016) solved the problem of drag on permeable sphere placed in micropolar fluid with non-zero boundary condition for microrotation and they observed that drag is greater in the case of zero micro-rotation vector than in the case of non-zero micro-rotation vector. Later on they (2017) also considered the problem of motion of a permeable shell in a spherical container filled with micropolar fluid.…”
Section: Introductionmentioning
confidence: 99%